2016
DOI: 10.1002/aenm.201601733
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineered Phthalocyanines as Hole‐Transporting Materials in Perovskite Solar Cells Reaching Power Conversion Efficiency of 17.5%

Abstract: intense panchromatic absorption [4] and high charge carrier mobilities. [5] In addition, their band gap can be easily tuned by simple variation of their ionic composition. [6] For example, a mixed-ion perovskite obtained as a mixture of formamidinium (FA) lead iodide and methy lammonium (MA) lead bromide, [FAPbI 3 ] 0.85 [MAPbBr 3 ] 0.15 , delivered the best to date energy conversion efficiencies of over 21% and revealed promising stability and reproducibility. [7-9] All the above mentioned, together with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 32 publications
2
83
0
Order By: Relevance
“…Recently, Torres and Nazeeruddin et al. reported a high PCE value of 15.5 % by using ZnPcs substituted with 5‐hexyl‐2,2′‐bisthiophenes as HTMs in PSCs . They found that the π‐π stacking of ZnPcs in the HTM layer greatly enhanced the PCE values of PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Torres and Nazeeruddin et al. reported a high PCE value of 15.5 % by using ZnPcs substituted with 5‐hexyl‐2,2′‐bisthiophenes as HTMs in PSCs . They found that the π‐π stacking of ZnPcs in the HTM layer greatly enhanced the PCE values of PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…[9,[18][19][20] However,t he solubility of CuPc in common organic solvents is rather poor.T herefore, it hast ob et hermally evaporated under high vacuum in these PSC devices,w hich results in additional production costs. [23] Triphenylamine (TPA) is aw ell-known electron donora nd has been widely used in small-molecule-based HTMs. [21,22] Very recently,m olecularly engineered zinc phthalocyanines (ZnPcs) have been developed as solutionprocessable HTMs in PSCs with an maximum PCE of 17.5 %.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to ensure low‐cost perovskite solar cell manufacturing, an ideal HTM candidate has to be easily affordable by simple synthetic schemes with minimized number of steps and easy workup and purification procedures for cost‐effective upscale. To date, molecular spiro‐type HTMs spiro‐OMeTAD [2,2′,7,7′‐tetrakis‐( N , N ‐di‐4‐methoxyphenylamino)‐9,9′‐spirobifluorene], FDT {2′,7′‐bis[bis(4‐methoxyphenyl)amino]spiro[cyclopenta(2,1‐b:3,4‐b′)dithiophene‐4,9′‐fluorene]}, and DDOF {2,2’,7,7′‐tetrakis‐( N , N ′‐di‐4‐methoxyphenylamine)dispiro‐[fluorene‐9,4′‐dithieno(3,2‐c:2′,3′‐e)oxepine‐6′,9′′‐fluorene]} reached the highest reported values over 19 % along with various other small‐molecule HTMs based on paracyclophane, truxene, benzotrithiophene, fluorene, carbazole, triazatruxene, anthratetrathiophene, phthalocyanine, indoloindole, and phenothiazine, successfully reaching comparably high photovoltaic performance. However, there are still only very few examples with a particular emphasis on low‐cost and highly efficient molecular HTMs such as spiroxanthene‐, fluorene‐, carbazole‐, and bifluorene‐based compounds including recently reported KR216 based on bifluorenylidene, and obtained by straightforward strategies showing that proper molecular engineering may be very fruitful toward low‐cost commercial solar cell application.…”
Section: Introductionmentioning
confidence: 99%